Structure of exotic three-body systems - Frederico, T.; Yamashita, Marcelo Takeshi [UNESP]; Delfino, A.; Tomio, L. (Springer, 2006)
The classification of large halos formed by two identical particles and a core is systematically addressed according to interparticle distances. The root-mean-square distances between the constituents are described by universal scaling functions obtained from a renormalized zero-range model. Applications for halo nuclei, Li-11 and Be-14, and for atomicn He-4(3) are briefly discussed. The generalization to four-body systems is proposed.